Luật tỏ̂ chức Viện kiẻ̂m sát nhân dân : (cộng bộ ngay 26-7-1960) (Vietnamese law coll. (Harvard Law School), 1962)
Various laws and regulations about the organization of Viện kiẻ̂m sát nhân dân tó̂i cao (= Supreme People's Procuracy of Vietnam), responsible for prosecutions and legal matters, what is equivalent to the Attorney General's office in western countries.